Bond strength of aged provisional 3D-printed methacrylate resin with different surface treatments and repair materials - Nutthawat Taokhampu; Hathairat Lekatana; Jadesada Palasuk (BMC Oral Health)
Abstract Background The provisional 3D-printed methacrylate resin is progressively used due to its superior accuracy and durability compared to traditionally fabricated provisional restorations. However, chairside modifications remain necessary to enhance marginal adaptation, esthetics, and functionality. This study aimed to evaluate the effect of surface treatments and repair materials on shear bond strength (SBS) of aged provisional 3D-printed methacrylate resin. Methods A total of 120 specimens (20 mm in diameter and 15 mm in height) were designed, printed using a DLP resin-based 3D printer, and aged by thermocycling for 1,500 cycles. Specimens (n = 10) were divided into four groups based on surface treatments: no surface treatment (negative control, NC), airborne particle abrasion (Al2O3), universal adhesive application (Adh), and airborne particle abrasion followed by the application of universal adhesive (Al2O3/Adh). Then, specimens were bonded using one of three repair materials: polymethyl methacrylate (PMMA), bis-acryl composite, and flowable composite. After 24 h, SBS was tested using a universal testing machine at a crosshead speed of 0.5 mm/min. Failure modes were examined using a stereomicroscope (20× magnification). The data were analyzed using the Kruskal-Wallis test, followed by Dunn’s test with a Bonferroni correction for multiple comparisons (p < 0.05). Results Flowable composite exhibited the highest SBS when aged provisional 3D-printed methacrylate resin was treated with Al2O3/Adh, Al2O3, and Adh, respectively, with no significant difference among these groups (p > 0.05). The lowest SBS was observed in NC, regardless of repair materials. Failure mode analysis was predominantly adhesive failure in the NC group, whereas cohesive and mixed failures were more common in the groups treated with Al2O3, Adh, and Al2O3/Adh, which were associated with improved bond strength. Conclusion To achieve the optimal SBS between aged provisional 3D-printed methacrylate resin and repair/reline materials, surface preparation with Al₂O₃/Adh, Al₂O₃, or Adh followed by flowable composite is recommended. Clinical significance In clinical settings where airborne particle abrasion is unavailable or impractical, applying universal adhesive followed by flowable composite provides reliable bond strength to aged 3D-printed methacrylate resin. However, omitting surface treatment entirely is not recommended due to the significantly reduced bond strength.